A refuse management system and blockchain: a practical view - Sham, Rohana; Amir Hussin, Amir 'Aatieff; Abdamia, Noranita; Mohamed, Suhana; Won, Jet Rou (World Academy of Research in Science and Engineering, 2020)
The refuse management in Malaysia had experienced high degradation, and this had caused a massive loss of ecosystem services due to significant pollution. Added with low community engagement to clean the environment, a lot of refuse management system being developed through apps is left unattended by them. One of the significant drawbacks of today refuses management system are still lacking in terms of the identity protocol for identifying individual especially those who have signed up for the app's usage. Apart from that, leakage of user identity has become a critical issue affecting users’ certain level to use the app as main tools under a refuse management system. As a result, most of the service providers need to build and maintain their own databases of user information for all kind of system they developed. Therefore, the objective of the study is to identify major security issue and inadequacy of the current blockchain mechanism in the refuse management system and to explore why blockchain mechanism should be used as a mechanism for higher authentication security in refuse management system. Thus, this project will demonstrate the potential of why blockchain should be used as a mechanism for in cleaning up the environment. The ultimate outcome looks at the potential blockchain application in refuse management system for the utilizing of the surrounding committee to clean the environment.